2022
DOI: 10.3389/fimmu.2022.871542
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Multiple Causes of Cardiac Death After the First Infusion of Atezolizumab: Histopathological and Immunohistochemical Findings

Abstract: Immune checkpoint inhibitors are promising agents for anticancer therapy. But despite their high efficacy in the treatment of solid tumors, there is still a problem with immune-related adverse events, especially cardiovascular complications with a very high mortality rate. Myocarditis or ischemic heart disease progression is not the only possible cause of cardiovascular death in patients treated with checkpoint inhibitors. We report a case of a patient with mucinous carcinoma of the lung, with a previous histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
0
0
Order By: Relevance
“…Also, treatments like the immunotherapy drug atezolizumab, used for NSCLC, have been linked to CAD, even though the primary risk with immunotherapy is myopericarditis. Autopsies of patients who passed away after receiving atezolizumab have shown instances of coronary artery tumor embolization [ 36 ]. On another note, certain tyrosine kinase inhibitors (TKIs), such as the EGFR inhibitor osimertinib, are known for their cardiotoxic effects but do not seem to significantly increase the risk of CAD [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…Also, treatments like the immunotherapy drug atezolizumab, used for NSCLC, have been linked to CAD, even though the primary risk with immunotherapy is myopericarditis. Autopsies of patients who passed away after receiving atezolizumab have shown instances of coronary artery tumor embolization [ 36 ]. On another note, certain tyrosine kinase inhibitors (TKIs), such as the EGFR inhibitor osimertinib, are known for their cardiotoxic effects but do not seem to significantly increase the risk of CAD [ 37 ].…”
Section: Reviewmentioning
confidence: 99%
“…Salem et al reported that mortality from myocarditis is as high as 50% (5). Ekaterina et al reported that a patient with previous hypertension and moderate left ventricular dysfunction died from severe adverse effects after the first infusion of atezolizumab, with a histopathological diagnosis of myocarditis, tumour coronary artery embolization, and micrometastases of myocardial mucus carcinoma; high expression of PD-1 in the myocardial area without tumour cells was also detected (6). Although the cause of death cannot be completely attributed to ICIs, judging from the histopathological diagnosis and the high detection results of PD-L1, the use of atezolizumab aggravated the patient's diagnosis and contribute to death.…”
mentioning
confidence: 99%